Quantitative assessment of pelvic floor muscle extensibility in pregnant women with a perineal elasticity meter. (1st November 2020) - Paschoal, Aline; Zanetti, Miriam Raquel Diniz; Petricelli, Carla Dellabarba; Alexandre, Sandra Maria; Araujo Júnior, Edward; Nakamura, Mary Uchiyama
Abstract: Objective: The objective of this study was to compare measurements of pelvic floor muscle extensibility in pregnant women obtained through the Epi-no ® and perineal elasticity meter (PEM) devices. Methods: This was an observational, cross-sectional study with a consecutive sample, conducted in a prenatal care outpatient clinic. The pelvic floors of 62 healthy pregnant women with gestational ages between 35 and 40 weeks were assessed. Perineal extensibility was measured using the Epi-no ® and PEM devices. Through the linear regression method, a formula was created to calculate the Epi-no ® values from the PEM values. To determine the degree of relationship between both variables, Pearson's correlation coefficient was used. Results: In the comparison of the results for 62 pregnant women using the two perineal extensibility assessment methods, the value obtained in the Pearson correlation coefficient analysis (0.621) indicated a moderate relationship between the variables. This finding was not confirmed by the Kappa correlation test. When the measurements were classified into three groups, a slight correlation was identified (perineum with restrictions, moderate extensibility, and good extensibility). Conclusion: There was a relationship between Epi-no ® and PEM from slight to moderate agreement.